Preparation method and application of high-strength light building material
By using a combination of machined sand, dolomite powder, fiber material and phosphogypsum in building materials, the problem of difficulty in combining high strength, lightweight and versatility in existing building materials is solved, and efficient and economical versatile building materials preparation is achieved.
Patent Information
- Application Number
- CN202411862260.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for existing building materials to have high strength, lightweight and versatile functions, such as breathing, electromagnetic shielding, anti-bacterial, sterilization, anti-static, ray-proof, waterproof, mildew-proof, fireproof, self-cleaning, and intelligence.
Machined sand and dolomite powder are used as aggregates, combined with polyvinyl alcohol fiber, glass fiber and carbon fiber as fiber materials, and added phosphogypsum components. High-strength and lightweight building materials are prepared through mechanical mixing, hot pressing and other processes.
The compressive strength and flexural strength of the material are improved, while reducing production costs, realizing the preparation of versatile building materials.
Smart Images

Figure CN119661178A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a preparation method and application of a high-strength lightweight building material. Background Art
[0002] With the improvement of people's living standards and the development of construction technology, the requirements for the functions of building materials are getting higher and higher, requiring new building materials to develop from a single function to a multi-functional direction, that is, building materials are required to not only meet general use requirements, but also have breathing, electromagnetic shielding, antibacterial, sterilization, antistatic, radiation protection, waterproof, mildew-proof, fireproof, self-cleaning, intelligence and other functions. Among them, the high strength and lightweight of building materials have become a development trend. Lightweight mainly refers to the porous material and low volume density. The use of lightweight materials such as hollow bricks and aerated concrete blocks can greatly reduce the dead weight of the building and meet the requirements of the development of the building towards space. High strength mainly refers to the strength of the building material is not less than 60MPa. The application of high-strength materials in load-bearing structures can reduce the cross-sectional area of the material and improve the stability and flexibility of the building. In summary, effectively improving the high strength and lightweight performance of building materials is an inevitable development result in the future.
[0003] Therefore, we propose a preparation method and application of a high-strength lightweight building material to solve the above-mentioned problems.
[0004] The above information disclosed in this background technology is only used to increase the understanding of the background technology of the present invention and therefore, it may include information that does not constitute the prior art known to ordinary technicians in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a high-strength lightweight building material to solve the problems raised by the above background technology.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high-strength lightweight building material, comprising the following ingredients in parts by weight: 200-400 parts of cement, 100-200 parts of machine-made sand, 100-200 parts of dolomite powder, 50-200 parts of glass microspheres, 50-200 parts of phosphogypsum, 20-100 parts of red mud, 20-80 parts of polyvinyl alcohol fiber, 20-50 parts of glass fiber, 20-50 parts of carbon fiber, 10-20 parts of water reducer, 2-8 parts of defoamer, and 1000-1500 parts of water.
[0007] Preferably, the water reducer is a polycarboxylic acid high-efficiency water reducer.
[0008] The present invention also provides a method for preparing a high-strength lightweight building material, comprising the following steps:
[0009] S1: Deacidify the phosphogypsum to remove soluble impurities and organic impurities;
[0010] S2: Process the machine-made sand to a particle size of 1-2 mm, the dolomite powder to a particle size of 0.5-1 mm, the glass beads to a particle size of 0.1-0.2 mm, and the phosphogypsum to a particle size of 0.01-0.05 mm;
[0011] S3: mechanically mixing cement, machine-made sand, dolomite powder, glass beads, phosphogypsum and red mud, and mixing them evenly to obtain a mixture;
[0012] S4: Add the remaining raw materials into the reactor, mix and stir evenly, heat the reactor to 80-90°C, then add the mixed material into the reactor, keep warm and stir until the water is dry, discharge the material, and cool to room temperature to obtain the raw material;
[0013] S5: Put the raw material into a mold for hot pressing to obtain a finished material.
[0014] Preferably, in S1, the phosphogypsum is deacidified by a water washing method, and the water washing process conditions are: room temperature, liquid-to-solid volume mass ratio of 3 mL / g, and washing 3 times.
[0015] Preferably, in S3, the mechanical mixing time is 2-4 hours.
[0016] Preferably, in S4, the first stirring time is 1-2 h, and the second stirring time is 3-5 h.
[0017] Preferably, in S5, the hot pressing temperature is 90-100° C., and the hot pressing time is 2-4 hours.
[0018] The present invention also provides application of the finished material obtained by the preparation method in building materials.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention uses machine-made sand and dolomite powder as aggregates, polyvinyl alcohol fiber, glass fiber and carbon fiber as fiber materials, and adds phosphogypsum components, thereby improving the strength of the material and reducing the production cost.
[0021] (2) The present invention processes machine-made sand, dolomite powder, glass beads, and phosphogypsum in decreasing particle sizes, which can better fill the gaps between the materials, improve the step-by-step filling effect of the matrix, and thus increase the strength of the material.
[0022] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] Prepare the following ingredients:
[0027] 250 parts of ordinary Portland cement;
[0028] 120 parts of machine-made sand;
[0029] 120 parts of dolomite powder;
[0030] Glass beads 100 parts;
[0031] 100 parts of phosphogypsum;
[0032] 30 parts of red mud;
[0033] 40 parts of polyvinyl alcohol fiber, fiber length 12mm, diameter 40μm;
[0034] Glass fiber 30 parts;
[0035] 30 parts of carbon fiber;
[0036] 10 parts of polycarboxylate high-efficiency water reducer;
[0037] 4 parts of defoamer;
[0038] 1000 parts of water.
[0039] S1: Deacidification of phosphogypsum is carried out by water washing method. The water washing process conditions are: room temperature, liquid-to-solid volume mass ratio of 3 mL / g, washing 3 times, and removing soluble impurities and organic impurities;
[0040] S2: Process the machine-made sand to a particle size of 1-2 mm, the dolomite powder to a particle size of 0.5-1 mm, the glass beads to a particle size of 0.1-0.2 mm, and the phosphogypsum to a particle size of 0.01-0.05 mm;
[0041] S3: Mechanically mix cement, machine-made sand, dolomite powder, glass beads, phosphogypsum and red mud for 2 hours to obtain a mixture;
[0042] S4: Add the remaining raw materials into the reactor, mix and stir evenly for 1 hour, heat the reactor to 80°C, then add the mixture into the reactor, keep warm and stir for 3 hours until the water is dry, discharge the material, cool to room temperature, and obtain the raw material.
[0043] S5: placing the raw material into a mold for hot pressing at a temperature of 90° C. for 2 h to obtain a finished material.
[0044] Example 2
[0045] Prepare the following ingredients:
[0046] 300 parts of ordinary Portland cement;
[0047] 150 parts of machine-made sand;
[0048] 150 parts of dolomite powder;
[0049] Glass beads 150 parts;
[0050] 150 parts of phosphogypsum;
[0051] 50 parts of red mud;
[0052] 60 parts of polyvinyl alcohol fiber, fiber length 12mm, diameter 40μm;
[0053] Glass fiber 40 parts;
[0054] Carbon fiber 40 parts;
[0055] 15 parts of polycarboxylate high-efficiency water reducer;
[0056] 6 parts of defoaming agent;
[0057] 1200 parts of water.
[0058] S1: Deacidification of phosphogypsum is carried out by water washing method. The water washing process conditions are: room temperature, liquid-to-solid volume mass ratio of 3 mL / g, washing 3 times, and removing soluble impurities and organic impurities;
[0059] S2: Process the machine-made sand to a particle size of 1-2 mm, the dolomite powder to a particle size of 0.5-1 mm, the glass beads to a particle size of 0.1-0.2 mm, and the phosphogypsum to a particle size of 0.01-0.05 mm;
[0060] S3: Mechanically mix cement, machine-made sand, dolomite powder, glass beads, phosphogypsum and red mud for 3 hours to obtain a mixture;
[0061] S4: Add the remaining raw materials into the reactor, mix and stir evenly for 2 hours, heat the reactor to 90°C, then add the mixture into the reactor, keep warm and stir for 4 hours until the water is dry, discharge the material, cool to room temperature, and obtain the raw material.
[0062] S5: placing the raw material into a mold for hot pressing at a temperature of 100° C. for 3 h to obtain a finished material.
[0063] Example 3
[0064] Prepare the following ingredients:
[0065] 350 parts of ordinary Portland cement;
[0066] 180 parts of machine-made sand;
[0067] 180 parts of dolomite powder;
[0068] 200 parts of glass beads;
[0069] 200 parts of phosphogypsum;
[0070] 100 parts of red mud;
[0071] 80 parts of polyvinyl alcohol fiber, fiber length 12 mm, diameter 40 μm;
[0072] Glass fiber 50 parts;
[0073] Carbon fiber 50 parts;
[0074] 20 parts of polycarboxylate high-efficiency water reducing agent;
[0075] 8 parts of defoaming agent;
[0076] 1500 parts of water.
[0077] S1: Deacidification of phosphogypsum is carried out by water washing method. The water washing process conditions are: room temperature, liquid-to-solid volume mass ratio of 3 mL / g, washing 3 times, and removing soluble impurities and organic impurities;
[0078] S2: Process the machine-made sand to a particle size of 1-2 mm, the dolomite powder to a particle size of 0.5-1 mm, the glass beads to a particle size of 0.1-0.2 mm, and the phosphogypsum to a particle size of 0.01-0.05 mm;
[0079] S3: Mechanically mix cement, machine-made sand, dolomite powder, glass beads, phosphogypsum and red mud for 4 hours to obtain a mixture;
[0080] S4: Add the remaining raw materials into the reactor, mix and stir evenly for 2 hours, heat the reactor to 90°C, then add the mixture into the reactor, keep warm and stir for 5 hours until the water is dry, discharge the material, and cool to room temperature to obtain the raw material;
[0081] S5: placing the raw material into a mold for hot pressing at a temperature of 100° C. for 4 h to obtain a finished material.
[0082] Benchmark Example 1
[0083] The difference between Baseline Example 1 and Example 1 is that in Baseline Example 1, the machine-made sand is replaced with commonly used quartz sand, the dolomite powder is replaced with commonly used limestone powder, and the polyvinyl alcohol fiber, glass fiber and carbon fiber are replaced with commonly used polyethylene fiber and polypropylene fiber, of which the polyethylene fiber is 50 parts and the polypropylene fiber is 50 parts.
[0084] Comparative Example 1
[0085] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the machine-made sand is replaced with quartz sand, and the particle size of the quartz sand is 0-0.6 mm.
[0086] Comparative Example 2
[0087] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 1, the machine-made sand is replaced by river sand, and the particle size of the river sand is 0 to 0.6 mm.
[0088] Comparative Example 3
[0089] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, dolomite powder is replaced by limestone powder, and the main component of the limestone powder is CaCO3.
[0090] Comparative Example 4
[0091] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, the dolomite powder is replaced by granite porphyry powder, and the main components of the granite porphyry powder are SiO2 and Al2O3.
[0092] Comparative Example 5
[0093] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, dolomite powder is replaced with quartz powder, and the main component of the quartz powder is SiO2.
[0094] Comparative Example 6
[0095] The difference between Comparative Example 6 and Example 1 is that in Comparative Example 6, the polyvinyl alcohol fiber, glass fiber and carbon fiber are replaced by polyethylene fiber and polypropylene fiber, respectively, wherein the polyethylene fiber is 50 parts and the polypropylene fiber is 50 parts, the polyethylene fiber is 12 mm in length and 24 μm in diameter, and the polypropylene fiber is 12 mm in length and 34 μm in diameter.
[0096] Comparative Example 7
[0097] The difference between Comparative Example 7 and Example 1 is that no phosphogypsum is added in Comparative Example 7.
[0098] The main raw materials for the above example are shown in the following table:
[0099]
[0100]
[0101] The dosage of water reducer and defoamer is based on the different stone powder and dosage slurry to achieve the same fluidity. The samples made in the above examples are subjected to compression and flexural tests respectively:
[0102] The compression test uses a cubic specimen, and the loading instrument uses a YAW4306 microcomputer-controlled electro-hydraulic servo pressure testing machine; the flexural test uses a prismatic specimen, and the loading instrument uses a WHY-300 / 10 microcomputer-controlled pressure testing machine. The test results are shown in the following table:
[0103]
[0104]
[0105] It can be seen from the above table that the compressive strength and flexural strength of different types of aggregates (machine-made sand, quartz sand, river sand) are as follows: the compressive strength and flexural strength of Example 1, Comparative Example 1, and Comparative Example 2 all show a decreasing trend, and the 60d compressive strength of Example 1 is increased by 20.44% and 10.83% compared with that of Comparative Example 1;
[0106] The compressive strength and flexural strength of different types of aggregates (dolomite powder, limestone powder, quartz powder, granite porphyry powder) were tested: the compressive strength and flexural strength of Example 1, Comparative Example 3, Comparative Example 4, and Comparative Example 5 all showed a decreasing trend. This is because among the four types of stone powders, dolomite powder is the finest, followed by limestone powder, followed by granite porphyry powder and quartz powder. The fine stone powder particles can better fill the gaps between the materials and improve the step-by-step filling effect of the matrix. The finer the stone powder particles, the more obvious the nucleation effect is, which increases the compressive strength.
[0107] The compressive strength and flexural strength of different types of fibers (polyvinyl alcohol fiber, glass fiber and carbon fiber / polyethylene fiber and polypropylene fiber) were tested: the compressive strength and flexural strength of Example 1 and Comparative Example 6 both showed a decreasing trend. The 60d compressive strength of Example 1 was increased by 19.32% and the 60d compressive strength was increased by 25.07% compared with that of Comparative Example 6.
[0108] The compressive strength and flexural strength of the test were tested with or without the addition of phosphogypsum: the compressive strength and flexural strength of Example 1 and Comparative Example 7 both showed a decreasing trend, and the 60d compressive strength of Example 1 was increased by 21.79% and 12.99% compared with that of Comparative Example 7.
[0109] In summary, the present invention uses machine-made sand and dolomite powder as aggregates, polyvinyl alcohol fiber, glass fiber and carbon fiber as fiber materials, and adds phosphogypsum components, which helps to improve the compressive strength and flexural strength of the material.
[0110] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0111] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A high-strength lightweight building material, characterized in that: The invention comprises the following ingredients in parts by weight: 200-400 parts of cement, 100-200 parts of machine-made sand, 100-200 parts of dolomite powder, 50-200 parts of glass beads, 50-200 parts of phosphogypsum, 20-100 parts of red mud, 20-80 parts of polyvinyl alcohol fiber, 20-50 parts of glass fiber, 20-50 parts of carbon fiber, 10-20 parts of water reducer, 2-8 parts of defoamer and 1000-1500 parts of water.
2. A high-strength lightweight building material according to claim 1, characterized in that: The water reducer is a polycarboxylic acid high efficiency water reducer.
3. A method for preparing a high-strength lightweight building material according to any one of claims 1 to 2, characterized in that: The steps include: S1: Deacidify the phosphogypsum to remove soluble impurities and organic impurities; S2: Process the machine-made sand to a particle size of 1-2 mm, the dolomite powder to a particle size of 0.5-1 mm, the glass beads to a particle size of 0.1-0.2 mm, and the phosphogypsum to a particle size of 0.01-0.05 mm; S3: mechanically mixing cement, machine-made sand, dolomite powder, glass beads, phosphogypsum and red mud, and mixing them evenly to obtain a mixture; S4: Add the remaining raw materials into the reactor, mix and stir evenly, heat the reactor to 80-90°C, then add the mixed material into the reactor, keep warm and stir until the water is dry, discharge the material, and cool to room temperature to obtain the raw material; S5: Put the raw material into a mold for hot pressing to obtain a finished material.
4. The method for preparing a high-strength lightweight building material according to claim 3, characterized in that: In S1, the phosphogypsum is deacidified by water washing, and the water washing process conditions are: room temperature, liquid-to-solid volume mass ratio of 3 mL / g, and washing 3 times.
5. The method for preparing a high-strength lightweight building material according to claim 3, characterized in that: In S3, the mechanical mixing time is 2-4 hours.
6. The method for preparing a high-strength lightweight building material according to claim 3, characterized in that: In S4, the first stirring time is 1-2 hours, and the second stirring time is 3-5 hours.
7. The method for preparing a high-strength lightweight building material according to claim 3, characterized in that: In S5, the hot pressing temperature is 90-100° C., and the hot pressing time is 2-4 hours.
8. Use of the finished material obtained by the method for preparing a high-strength lightweight building material as claimed in any one of claims 3 to 7 in building materials.